2004
DOI: 10.1038/sj.onc.1208160
|View full text |Cite
|
Sign up to set email alerts
|

Src family kinases, key regulators of signal transduction

Abstract: The Src family of protein tyrosine kinases (SFKs) plays key roles in regulating signal transduction by a diverse set of cell surface receptors in the context of a variety of cellular environments. SFKs have evolved many ingenious molecular strategies to couple receptors with the cytoplasmic signaling machinery. The contributions to this issue of ONCOGENE describe how this machinery regulates fundamental cellular processes, including cell growth, differentiation, cell shape, migration and survival, and speciali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
679
0
7

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 821 publications
(693 citation statements)
references
References 7 publications
7
679
0
7
Order By: Relevance
“…An interesting exception to this rule is the knockout of Src -deletion of the most highly connected protein in the adhesome results in viable mice suffering only from osteopetrosis 29 . This may be explained by compensation provided by other Src family members such as Lyn and Fyn 30 .…”
Section: Characteristics Of the Adhesome Networkmentioning
confidence: 99%
“…An interesting exception to this rule is the knockout of Src -deletion of the most highly connected protein in the adhesome results in viable mice suffering only from osteopetrosis 29 . This may be explained by compensation provided by other Src family members such as Lyn and Fyn 30 .…”
Section: Characteristics Of the Adhesome Networkmentioning
confidence: 99%
“…Several studies have shown that the non-receptor tyrosine kinase Src has important roles in numerous cellular processes, such as proliferation, survival, and cytoskeleton rearrangement [29]. Stimulation by 5-HT activated Src in endothelial cells through its receptor subtype HTR1B (Figs.…”
Section: -Ht Stimulates a Phosphorylation Signaling Cascade In Endotmentioning
confidence: 99%
“…Src family kinases (SFKs) comprise a subclass of membrane-associated non-receptor tyrosine kinases that are involved in a variety of cellular processes, such as cell division, motility, adhesion, angiogenesis and survival (5,6). Several of the SFKs have been shown to be upregulated in cancer and topromote progression and metastasis.…”
Section: Introductionmentioning
confidence: 99%